Tantalum: A transmogrifying material in dental implant - Meenakshi Akshaya Lingam; Ishwarya Balasubramanian (Wolters Kluwer Medknow Publications, 2021)
Prosthodontic rehabilitation with implants aims at enhancing patient's quality of life and prolongation of survival of prosthesis. Porous tantalum trabecular metal (PTTM ) - incorporated titanium (Ti) is used extensively in orthopedics, but clinical researches and reports in the applications of oral cavity are limited. Therefore, prospective clinical trials of PTTM-incorporated Ti implants are essential for future use in dentistry. In this article, corrosion resistance and biocompatibility of tantalum is discussed elaborately and the usage of PTTM along with Ti in several studies is reported.